2008
DOI: 10.1099/vir.0.2008/002048-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine patterns in a comparative model of arenavirus haemorrhagic fever in guinea pigs

Abstract: Arenaviruses such as Lassa virus cause a spectrum of disease in humans ranging from mild febrile illness to lethal haemorrhagic fever. The contributions of innate immunity to protection or pathogenicity are unknown. We compared patterns of expression of cytokines of innate immunity in mild versus severe arenavirus disease using an established guinea pig model based on the macrophage-tropic arenavirus Pichinde virus (PICV). Cytokine transcripts were measured by using real-time RT-PCR in target organs and blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 54 publications
(48 reference statements)
2
19
0
Order By: Relevance
“…We use a safe small animal model, in which two PICV strains derived from low (P2) and high (P18) passages in guinea pigs can respectively cause avirulent and virulent infections with opposing outcomes in the animals, to characterize the virulence-associated determinants in arenavirus genome. Compared to the variable mortality rates of outbred guinea pigs infected with virulent PICV in previous studies (Jahrling et al, 1981; Scott and Aronson, 2008), we have observed more consistent high mortality rate and hemorrhagic fever symptoms in our infected animals (Figs 3–5), which is likely due to different experimental settings between our study and others. Knowledge of virulence mechanisms learned from the PICV-guinea pig model can be extrapolated to other pathogenic arenaviruses in humans.…”
Section: Discussionsupporting
confidence: 65%
“…We use a safe small animal model, in which two PICV strains derived from low (P2) and high (P18) passages in guinea pigs can respectively cause avirulent and virulent infections with opposing outcomes in the animals, to characterize the virulence-associated determinants in arenavirus genome. Compared to the variable mortality rates of outbred guinea pigs infected with virulent PICV in previous studies (Jahrling et al, 1981; Scott and Aronson, 2008), we have observed more consistent high mortality rate and hemorrhagic fever symptoms in our infected animals (Figs 3–5), which is likely due to different experimental settings between our study and others. Knowledge of virulence mechanisms learned from the PICV-guinea pig model can be extrapolated to other pathogenic arenaviruses in humans.…”
Section: Discussionsupporting
confidence: 65%
“…Because of the reported variability in lethality caused by PICV infection of outbred guinea pigs [32], [36], [37], [38], [39], we sought to establish a uniformly lethal model that would facilitate the evaluation of favipiravir. We prepared a virus stock from a single passage of the p18 guinea pig-adapted strain in Hartley guinea pigs.…”
Section: Resultsmentioning
confidence: 99%
“…PICV infection in guinea pigs has proven to be useful for the study of acute arenaviral disease [37], [38], [39], [44] and for preclinical efficacy evaluations [48], [49], as the virus can be handled safely in BSL-2 containment. There have been mixed reports on the lethality of guinea pig-adapted PICV in the readily available Hartley outbred guinea pig strain [32], [36], [37], [38], [39]. In addition to other factors, the variation in the stringency of the criteria used to define the terminal endpoints likely contributed to the reported variability.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical data match results with observations in primary human cells in vitro . In animal models of fatal LF [56,122,150,167] it also seems that higher levels of IL-8 are protective against LF in vivo . While cell culture studies [46] show that replication of LASV in monocyte-derived MPs or DCs is associated with suppressing innate immune responses, in vivo studies with patients or experimental animals show that cytokines such as IP-10 and IL-8 (possibly coming from uninfected bystander cells) can recruit immune cells and increase survival.…”
Section: Profiling Disease Progressionmentioning
confidence: 99%